Prevalence of Fabry Disease in Young Patients with Stroke in Argentina. - Reisin, Ricardo C. (2018)
Background: Fabry disease (FD) is an underdiagnosed cause of stroke in youngadults, but the frequency of this association is largely unknown. We estimatedthe prevalence of FD in a nationwide cohort of young adults who had stroke andtransient ischemic attack (TIA) in Argentina. Methods: This was a prospective, multicenterstudy of stroke and FD in young adults (18-55 years) conducted in Argentinabetween 2011 and 2015. Patients were enrolled if they had had a TIA or an ischemicor hemorrhagic stroke within the previous 180 days. FD was diagnosed bymeasuring α-galactosidase A activity (males) and through genetic studies (females).Results: We enrolled 311 patients (54% men, mean age: 41 years). Ischemic eventsoccurred in 89% of patients (80% infarcts, 9% TIA) and hemorrhagic strokes in11%. One female (.3% of the total group, 1% of the cryptogenic ischemic strokes)had the pathogenic mutation c.888G>A/p.Met296Ile /Exon 6 on the GAL gene.Her only other manifestation of FD was angiokeratoma. Eighteen females hadnonpathogenic intronic variations: c.-10C>T, c.-12G>A, or both. Two patients hadthe nonpathogenic mutation D313Y, while a third had the likely benign mutationS126G. Conclusions: FD was identified in 1 patient (.3%) in this first LatinAmerican study. The patient presented with a late-onset oligo-symptomatic formof the disease. A large number of nonpathogenic mutations were present in ourcohort, and it is essential that they not be mistaken for pathogenic mutations to avoid unnecessary enzyme replacement treatment.